HUBUNGAN ANTARA LITERASI DIGITAL DENGAN PENGGUNAAN MEDIA SOSIAL MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM SEKOLAH TINGGI AGAMA ISLAM “UISU” PEMATANG SIANTAR - Isnaini Syahfira; Yusra Dewi Siregar; Franindya Purwaningtyas (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
This research is motivated by the current phenomenon where according to a Digital Literacy survey conducted by Katadata, 30-60% of Indonesian people have been exposed to hoaxes when using social media anda 11% of them have spread hoax information because they don’t care about the truth of the information being spread. This study aimed to determine the relationship beetwen digital literacy and social media use. This study uses a quantitative approach, the population of this study was all students of the PAI study program of STAI “UISU” Pematang Siantar. The sample size was deterrmined using a purposive sampling technique. The sample size was determined using the Slovin formula so that the number of respondents was 86. Research data were collected by distributing questionnairs. The results showed that the digital literacy of PAI STAI “UISI” Pematang Siantar students was categorized as very high. This obtained an average score of 4.23 on an interval scale of 4.21-5.00, as well as the use of social media by students of PAI STAI “UISU” Pematang Siantar is categorized as good, it obtained an average score of 3.92 on an interval scale 3.21-4.21. the result of the data analysis also show that there is asignificant relationship between digital literacy and the use of social media by students of the PAI study program of STAI “UISU” Pematang Siantar.